Spheres of maximum electromagnetic chirality - Jorge Olmos-Trigo; Manuel Nieto-Vesperinas; Gabriel Molina-Terriza (Physical Review Research)
The search for objects that yield maximum electromagnetic chirality in their emitted wave field has gathered significant attention in recent years. However, achieving such maximum chirality is challenging, as it typically requires complex chiral metamaterials. Here, we demonstrate that chiral spheres can yield maximum chirality in their emitted wave field. Specifically, we analytically find the spectral trajectories at which chiral spheres become optically transparent to a given helicity of the incident field, while for its opposite helicity, they behave as dual objects, i.e., on scattering, they preserve helicity. Since chiral spheres behave as dual objects at the first Kerker condition of zero backscattering, we significantly simplify this condition in terms of a Riccati-Bessel function. Our analytical findings suggest the creation of spherical building blocks for designing metasurfaces or metamaterials with maximum electromagnetic chirality properties.